Lectora Inspire Features and Their Impact on Enhancing Grammar Comprehension at Sultan Aji Muhammad Idris Islamic State University, Samarinda - Sari, Devi Rafika; Saputra, Riski Janu; Taufiqurrochman, R.; Hilmi, Danial (Abjadia : International Journal of Education, 2023)
The study emphasizes the significance of Nahwu knowledge in enhancing Arabic language skills during the educational process, particularly at the Sultan Aji Muhammad Idris State Islamic University in Samarinda. Notably, Nahwu teachers encounter challenges related to time efficiency in teaching and limited learning resources for students. Concurrently, technological advancements offer solutions to these issues, promising improved time management and enhanced access to learning materials. In response, this research focuses on enriching Lectora Inspire's capabilities for Nahwu practice. The research adopts the Research and Development (R&D) approach, employing the ADDIE model. Data collection involves observation, interviews, questionnaires, and testing, with participants from the Arabic Language Teaching Department. The outcomes encompass the development of the Lectora Inspire method using the ADDIE model, including analysis, design, development, application, and evaluation stages. Validation results indicate the product's excellence, with high ratings from design and content experts, grammar teachers, and students. Furthermore, the effectiveness of utilizing Lectora Inspire for grammar exercises is demonstrated through t-test results, signifying a statistically significant improvement (Sig value of 0.017 < 0.05). This research contributes valuable insights into optimizing technology for Nahwu education, addressing challenges faced by teachers and students alike.